Jack Welch and the 4E's of leadership how to put GE's leadership formula to work in your organization - Krames, Jeffrey A. (McGraw-Hill, 2005)
Beyond the nuts and bolts of the 4e model, this book outlines a step-by-step blueprint anyone can follow to stock an organization with performance-ready leaders and leaders-in-training.